Роль семейного врача в профилактике и раннем выявлении рака шейки матки = Family Practitioner’s Role in Prevention and Diagnostics of Cervical Cancer - Lukyanchuk, O. V.; Velychko, V. I.; Danilchuk, G. A.; Kuzeva, N. G. (Journal of Education, Health and Sport, 2016)
Lukyanchuk O. V., Velychko V. I., Danilchuk G. A., Kuzeva N. G. Роль семейного врача в профилактике и раннем выявлении рака шейки матки = Family Practitioner’s Role in Prevention and Diagnostics of Cervical Cancer. Journal of Education, Health and Sport. 2016;6(4):45-62. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49413 http://ojs.ukw.edu.pl/index.php/johs/article/view/3446 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 10.04.2016. Accepted: 10.04.2016. Роль семейного врача в профилактике и раннем выявлении рака шейки матки Лукьянчук О. В., Величко В. И., Данильчук Г. А., Кузева Н. Г. Одесский национальный медицинский университет Резюме Рак шейки матки остается одним из наиболее распространенных онкологических заболеваний в женской популяции. Основной причиной развития предопухолевых и опухолевых заболеваний шейки матки, влагалища, полового члена, вульвы, гортани и др. является вирус папилломы человека. В настоящее время семейный врач играет важную роль как в организации выявления предопухолевой патологии репродуктивного тракта, так и в повышении образования населения относительно профилактики предопухолевых и опухолевых заболеваний шейки матки. Ключевые слова: рак шейки матки, вирус папилломы человека, семейный врач, диагностика, профилактика. Family Practitioner’s Role in Prevention and Diagnostics of Cervical Cancer Lukyanchuk O.V. Head of the Department of Reconstructive and Regenerative Medicine with a Course of Reproduction, oncogynecologyst, Ph.D. Velychko V.I. . Head of the Department of Family Medicine and General Practice, general practitioner, Prof., Ph.D. Danilchuk G.A. Assistant of the Department of Family Medicine and General Practice, general practitioner, Ph.D. Kuzeva N.G. Assistant of the Department of Reconstructive and Regenerative Medicine with a course of reproduction, gynecologist, Ph.D. Summary Cervical cancer remains one of the most frequent oncological diseases in the female part of the population. The main cause of precancerous and cancerous anomalies of the cervix, vagina, penis, pharynx etc. is Human papillomavirus. Family Practitioners currently play a leading role in organizing preventive measures for precancerous disorders of the reproductive tract and educating the population about prevention of cervical cancers. Keywords: cervical cancer, Human papillomavirus, Family Practitioner, diagnostics, prevention.